Improvement of 5, 6α-epoxycholesterol, 5, 6β-epoxycholesterol, cholestane-3β, 5α, 6β-triol and 6-oxo-cholestan-3β, 5α-diol recovery for quantification by GC/MS. (October 2017) - Soules, Regis; Noguer, Emmanuel; Iuliano, Luigi; Zerbinati, Chiara; Leignadier, Julie; Rives, Arnaud; de Medina, Philippe; Silvente-Poirot, Sandrine; Poirot, Marc
Highlights: Some [ 14 C]-epoxycholesterol metabolites were used to follow up their preparation for GC/MS analysis. Solvent extraction of TMS esters is the limiting step for 5, 6-EC and OCDO analysis. The yield of recovery for 5, 6α-EC, 5, 6β-EC and OCDO was drastically improved. Abstract: 5, 6α-epoxycholesterol (5, 6α-EC) and 5, 6β-epoxycholesterol (5, 6β-EC) are oxysterols involved in the anticancer pharmacology of the widely used antitumor drug tamoxifen. They are both metabolized into cholestane-3β, 5α, 6β-triol (CT) by the cholesterol-5, 6-epoxide hydrolase (ChEH) enzyme, and CT is metabolized by an as-yet uncharacterized enzyme into 6-oxo-cholestan-3β, 5α-diol (OCDO). A recent feasibility study showed that the 5, 6-ECs may represent surrogate markers of tamoxifen activity in breast cancer patients undergoing endocrine therapy, thus there is a growing interest in their accurate quantification. These oxysterols are usually quantified by gas-liquid chromatography coupled to mass spectrometry (GC/MS), using an isotope dilution methodology with the corresponding deuterated oxysterol. This method is considered to be relative quantitative since all of the standards used are deuterated oxysterols, however it is not known whether the preparation of each oxysterol is affected in the same way by the extraction, pre-purification by solid phase extraction (SPE) and trimethylsilylation steps, particularly when using biological samples that contain many other reactive compounds. Thus, in this study we investigated the yield of the 5, 6-ECs, CT and OCDO recovery from patient serum samples at different stages of their work-up and trimethylsilylation prior to GC/MS analysis, using [ 14 C]-labeled analogs to follow these oxysterols at each step. We measured a 40 to 60% loss of material for the 5, 6-ECs and OCDO, however we also describe the conditions that improved their recovery. Our data also show that the use of deuterated 5, 6α-EC, 5, 6β-EC, CT and OCDO is an absolute requirement for their accurate quantification.